COGNITIVE CHARACTERISTICS OF EXPRESSIONS EXPRESSING THE CONCEPT OF "EDAD" IN SPANISH - Achilova Zulxumor Pulаtovna (PEDAGOGS, 2024)
This scientific article is devoted to the study of the semantics of linguistic units of the Spanish language that verbalize the concept “Edad” and to the study of the cognitive foundations of the conceptualization of human age states. The study was carried out within the framework of the semantic-cognitive direction, which considers the analysis of linguistic means representing concepts as one of the ways to describe human mental activity. Issues of linguistic representation of human age-related states are of growing interest from researchers. The attention of scientists to the study of the peculiarities of linguistic objectification of age concepts is due, in particular, to the fact that the category of age, being closely related to the category of time, is one of the ontological categories that determine human life. A person’s age is time in its immediate reality for a person, “from within, the time of existence we experience existentially, which represents its own value” [Pigrov 2017: 9]